THE USE OF HYPONYMIC UNITS IN MILITARY-PATRIOTIC SPEECH - Murodova Firuza Jalolovna (Modern American Journals, 2025)
This article analyzes the role and functional features of hyponymic units in military-patriotic speech. Hyponymy is classified as a linguistic phenomenon, and the semantic relations of lexical units with military-patriotic content are revealed. The article highlights the connections between hyponyms and hypernyms, their forms of expression in speech, as well as their role in ensuring semantic clarity in context. The analysis is based on modern military texts and patriotic speeches, demonstrating the influence of the hyponymic system on speech style. The research results contribute to a deeper understanding of the semantic layer in military discourse.
Keywords: Hyponymy, hyponym and hyperonym term, central lexeme of the micro-system, implicit, semantic field, hierarchical relation, hyperonymic (genus-species) relation, partonymic (whole-part) relation.